Dealing with the high-risk potential of COVID-19 cross-infection in dental practice - Yulianto, Heribertus Dedy Kusuma; Purwanti, Nunuk; Utami, Trianna Wahyu; Dewi, Anne Handrini; Listyarifah, Dyah; Ruspita, Intan; Nur, Asikin; Susilowati, Heni (Majalah Kedokteran Gigi Indonesia, 2020)
The World Health Organization reported that the SARS-CoV-2 virus has infected more than 5 million people around the world. Dental care providers and health care professionals need to be aware of the high-risk potential of crossinfection since the routes of virus transmission commonly happen through droplets and aerosols. This review aimed at collecting essential knowledge about the COVID-19 needed by dental practitioners. The review focused on the oral involvement in COVID-19, the role of oral transmission as the high-risk potential of cross-infection and recommended strategies to minimize the risk of cross-infection in dental practice. We searched all the published clinical features from PubMed, Google Scholar, Scopus and hand searched library online databases, from January 2015 until May 2020. Keywords used were â€œCOVID-19â€, â€œDentistryâ€, â€œDental protectionâ€, â€œCross-contaminationâ€, â€œAerosol and non aerosolâ€, and â€Povidone-iodineâ€ with their combinations. We identified 52 articles to review after the initial selection with inclusion and exclusion criteria. Results showed use of topical applications of povidine-iodine and viricidal mouthwash could significantly reduce the high-risk of cross-infection from dentistry patients who are asymptomatic with COVID-19 infection. Further safeguards include suspending all non-emergency procedures temporarily and closely screening patients for symptoms which may be suspected to be COVID-19 infection.